Product optimization of a fed-batch fermentation process - Arshad, Ahmad; Noor Asma Fazli, Abdul Samad; Mohd Kamaruddin, Abd Hamid (2007)
This paper discusses the development of constrained optimization strategies for a fed-batch penicillin fermentation process. To facilitate the study, a mathematical model of the system is developed based on published materials, and simulated using MATLAB software. Good agreement is obtained when the results are validated against published work. To provide on-line estimates of the difficult to measure penicillin concentration, Partial Least Squares model is employed. Using these estimates, good control of product concentration is established thus enabling it to be implemented as part of product concentration control loop. Further improvements are introduced using dynamic optimization aiming at increasing the achievable product concentration while satisfying all process constraints. Two strategies are considered. These are optimal control policy using direct-shooting algorithm and unconstrained Dynamic Matrix Control (DMC). From this two optimization approaches, it is possible to estimate the optimal operating conditions as substrate feed rate so that the systems presents high performance within threshold value limit. The result also revealed that the use of DMC approach is superior the direct shooting method in term of the penicillin concentration as well as penicillin purity. Results obtained in this study have exposed the potentials of dynamic optimization schemes in improving the product purity in a fed-batch fermentation process.